Studi Empiris pada Pola Sumber Dana untuk Pembiayaan Usahatani Padi di Sumatera Selatan - Maryanah Hamzah; Agustina Bidarti; Erise Anggraini; Mirza Antoni (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Hamzah et al, 2018. Empirical Study on the Pattern of Funding Sources for Rice Farming in South Sumatra. JLSO 7(2):196-203. The objective of the study was to identify the source and size of the financing portion of the rice farming from the loan and the terms and the interest rate charged. The interviews were conducted on 75 samples of rice farmers whose farming costs were partly derived from loans at three different land ecosystems in South Sumatra Province. The three types of ecosystems viz., tidal swamp land, technical irrigation, and swamp land were used in the study. The results showed that there were seven financing sources that farmers used for fulfill their production cost if they not enough capital. Middlemen was biggest source with a portion of 45.28% and their own costs of 43.52, the rest is relatively small comes from money lenders, families, rice milling units, cooperative and friends. The interest rate charged varies from 3% to 50% per planting season. The lowest interest rate on lending money was to cooperatives and middlemen. However, if farmers borrow from middlemen, they must sell their rice to them. The highest interest rate from money lenders is 50%. All loans were being paid at after harvested time. Only borrow to families and friends were not charged interest and other terms. Farmers were forced to use non-formal lending institutions because banks located far away and they were afraid to come to the bank. It is suggested to reduce the dependence of rice farmers on non-formal lending institutions through developing a more effective agricultural cooperative.